Environmental impact analysis of lithium iron phosphate batteries for energy storage in China - Lin, Xin; Meng, Wenchuan; Yu, Ming; Yang, Zaimin; Luo, Qideng; Rao, Zhi; Zhang, Tiangang; Cao, Yuwei (Frontiers in Energy Research, 2024)
The deployment of energy storage systems can play a role in peak and frequency regulation, solve the issue of limited flexibility in cleaner power system in China and ensure the stability and safety of the power grid. This paper presents a comprehensive environmental impact analysis of lithium iron phosphate battery system for the storage and delivery of one kilowatt-hour electricity.Quantities of copper, graphite, aluminum, lithium iron phosphate and electricity consumption are set as uncertainty and sensitivity parameters with the variation of [90%, 110%]. Results show that global warming potential is 9.08E+01 kg CO2 eq. and fossil resource use is 1.21E+03 MJ with uncertainty range of [8.54E+01, 9.23E+01] and [1.15E+03, 1.23E+03] respectively. Electricity consumption during the manufacture and installation process is the greatest contributor to climate change (CO2 eq. emissions), accounting for 39.71% and largely owing to non-renewable sources, followed by cathode material at 27.85% and anode material at 18.36%. Disposal and recycling process offers emission reductions but requires an additional 1.17% use of fossil resources. Sobol T indices for quantity of electricity are the highest in acidification, climate change, fossil resource use and ionizing radiation. By considering the pathway of China's electricity mix from 2020 to 2050 under Paris Agreement's 2 degree target, the potential of environmental emission reduction of the system is evaluated. Results show that the greener electricity mix could lead to a 24.59% reduction in acidification impact, 35.74% in climate change impact, 33.24% in fossil resource use and 44.13% in ionizing radiation impact. This study offers a comprehensive view of the environmental impact reductions associated with the lithium iron phosphate battery and its industry.Moving towards carbon neutrality has become a consensus among major countries in the world. In recent years, the development of energy storage technology has become a key point in the global y 删除[Yuwei Cao]: 下标 设置格式[Yuwei Cao]: except for 删除[Yuwei Cao]: 删除[Yuwei Cao]: use and ozone depletion 删除[Yuwei Cao]: Quantity of aluminum and lion lithium iron phosphate are two dominate sensitivity parameters for ozone depletion. 删除[Yuwei Cao]: R 删除[Yuwei Cao]: of the C2°scenario 删除[Yuwei Cao]: can 删除[Yuwei Cao]: make 删除[Yuwei Cao]: